Job satisfaction, monetary return and promotion among International Islamic University Malaysia (IIUM) lectures - Akorede, Quadri Mojeed (Institute of Education, International Islamic Universiti Malaysia, 2012)
This study investigated job satisfaction. monetary return and promotion among IIUM lecturers in her Gombak campus. The study used one hundred and twenty five (125) lecturers drawn through purposive sampling across all the kuliyyah and institutes in her Gombak campus; the study examines monetary return and promotion (as independent variables) as predictors of job satisfaction (dependent variable) among IIUM lecturers. The results indicated that IIUM lecturers are moderately satisfied with their job in terms of monetary return and promotion. There is also statistical difference found among IIUM lecturers on promotion related to gender and year of service. Female lecturers are found to be more satisfied in terms of promotion than their male counterparts, lecturers who have spent between 1-lOyears are also found to be more satisfied than those who have spent above l lyears. It was also found that there are no significant differences among lecturers in terms of monetary return with regard to gender differences and number of years spent based on the comparison done between the genders, years of service means and the total means of the study.